Shared Decision Making and Effective Physician-Patient Communication: The Quintessence of Patient-Centered Care - Huy Ming Lim; Kristiana Siste Kurniasanti (University Library System, University of Pittsburgh, 2015)
The Institute of Medicine's (IOM) 2001 landmark report, Crossing the Quality Chasm: A New Health System for the 21st Century, identified patient-centeredness as one of the fundamental attributes of quality health care, alongside safety, effectiveness, timeliness, efficiency, and equity. The IOM defined patient-centeredness as "providing care that is respectful of and responsive to individual patient preferences, needs, and values and ensuring that patient values guide all clinical decisions." This concept of patient-centered care represents a paradigm shift from the traditional disease-oriented and physician-centered care, grounding health care in the subjective experience of illness and the needs and preferences of individual patients rather than the evaluation and treatment of diseases which emphasizes on leveraging clinical expertise and evidence derived from population-based studies. Regrettably, despite the ubiquitous talk about patient-centered care in modern health care, shared decision-making and effective physician-patient communication-the two cruxes of patient-centered care-are yet to become the norms. Strategies to promote and enhance shared decision-making and effective communication between clinicians and patients should be rigorously implemented to establish a health care system that truly values patients as individuals and turn the rhetoric of patient-centered care into reality.